Product Development and International Trade - Grossman, Gene M.; Helpman, Elhanan (Journal of Political Economy, 1989)
The authors develop a multicountry, dynamic general equilibrium model of product innovation and international trade to study the creation of comparative advantage through R$50D and the evolution of world trade over time. In their model, firms must incur resource costs to introduce new products, and forward-looking potential producers conduct R$50D and enter the product market whenever profit opportunities exist. Trade has both intraindustry and interindustry components, and the different incentives that face agents in different countries for investment and savings decisions give rise to intertemporal trade. The authors derive results on the dynamics of trade patterns and trade volume and on the temporal emergence of multinational corporations. Copyright 1989 by University of Chicago Press.